Results of Increasing Self- awareness on The T 2 DM Patients in Rattaphum Hospital, Rattaphum District, Songkhla Province - Theerangkara, Narayana (Journal of Health Science of Thailand, 2017)
This quasi-experimental study was aimed at evaluating of self-awareness on the type 2 diabetes mellitus (T2DM) patients both before and after receiving stimulant involved knowledge, understanding, self-awareness to complication, responsibility and the evaluation of level of HbA1c, during January 2010 to December, 2011. Comparison was made between a control group receiving standard treatment change with a study group. In all, 92 subject were randomly selected from T2DM patients ages 40-70 years with HbA1c level over 7 percent. The results showed that both experimental and control groups were mostly female a aged 60- 70 years old with levels of HbA1c more than 8 percents. The results showed that the mean difference of the level of HbA1c of the experimental groups and the control group was significant (p < 0.05). In conclusion stimulant involved knowledge, understanding, and self-awareness to complications and responsibility can induce decreasing level of HbA1c significantly. If improves in duration frequency, or content, beter HbA1c control can be expected.